Protein-Engineered Coagulation Factors for Hemophilia Gene Therapy - Samelson-Jones, Benjamin J.; Arruda, Valder R. (Molecular therapy. Methods & clinical development, 2019)
Hemophilia A (HA) and hemophilia B (HB) are X-linked bleeding disorders due to inheritable deficiencies in either coagulation factor VIII (FVIII) or factor IX (FIX), respectively. Recently, gene therapy clinical trials with adeno-associated virus (AAV) vectors and protein-engineered transgenes, B-domain deleted (BDD) FVIII and FIX-Padua, have reported near-phenotypic cures in subjects with HA and HB, respectively. Here, we review the biology and the clinical development of FVIII-BDD and FIX-Padua as transgenes. We also examine alternative bioengineering strategies for FVIII and FIX, as well as the immunological challenges of these approaches. Other engineered proteins and their potential use in gene therapy for hemophilia with inhibitors are also discussed. Continued advancement of gene therapy for HA and HB using protein-engineered transgenes has the potential to alleviate the substantial medical and psychosocial burdens of the disease.